Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1155/2022/9196913
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] The Spread, Rise, and Fall of University Students’ Interconnected Internet Public Opinion in the Age of Big Data

Abstract: With the interconnected network’s quick growth and widespread adoption, it has only made sense that it would serve as a hub for the dissemination of ideologies and cultural information as well as an amplifier for public opinion. The world is dualistic. The popularity of the connected network has both positive and negative effects on society. It makes people’s lives more convenient, but it also has some drawbacks. Public opinion will quickly build up on the interconnected network as network communication become… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Therefore, ideological and political education in colleges and universities should be combined with big data to guide college students’ outlook on life and values ( 12 ). In addition, colleges and universities should make full use of Internet tools to pay attention to student’s physical and mental health and behavior ( 13 ), so as to effectively use online public opinion to educate and guide them ( 14 ). Then, in the research on prediction and early warning of online public opinions in colleges and universities, it is mainly used to track and predict public opinions in a big data environment.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, ideological and political education in colleges and universities should be combined with big data to guide college students’ outlook on life and values ( 12 ). In addition, colleges and universities should make full use of Internet tools to pay attention to student’s physical and mental health and behavior ( 13 ), so as to effectively use online public opinion to educate and guide them ( 14 ). Then, in the research on prediction and early warning of online public opinions in colleges and universities, it is mainly used to track and predict public opinions in a big data environment.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%